Effects of EUV Irradiation on Poly-Si SONOS NVM Devices - Tsui, Bing-Yue; Yen, Chih-Chan; Li, Po-Hsueh; Lai, Jui-Yao (My University, 2011)
The effects of extreme-ultraviolet (EUV)-irradiation-induced damage on the characteristics of a silicon-oxide-nitride-oxide-silicon (SONOS) memory device are investigated. After EUV irradiation, changes in the memory window and program/erase speed indicate the generation of positive charges and new traps. Retention performance degrades after high-dose irradiation, which indicates that the tunneling layer is damaged. Endurance performance degrades severely because the damage in the blocking oxide results in serious electron back injection after cycling operations. These defects cannot be recovered after 600 degrees C annealing. It is recommended that in-process high-dose EUV irradiation on a SONOS stack after a front-end-of-line process should be avoided.
Keywords: Extreme ultraviolet lithography (EUVL); nonvolatile memory (NVM); radiation damage; silicon-oxide-nitride-oxide-silicon (SONOS) memory